DEVELOPMENT OF COMPETENCE OF FUTURE TEACHERS AS A PEDAGOGICAL PROBLEM - Baxronova Marjona San`atovna (Web of Journals Publishing, 2024)
Through this article, it is now covered that the qualitative and effective conduct of teacher activities is the main pedagogical problem before them, along with the development of our society and the development of growing young people as a harmonious mature person with every completion, as well as the responsible work of pedagogical staff.
Keywords: Pedagogical ability, competence, professional competence, pedagogical problem.